1998
DOI: 10.1007/s005950050156
|View full text |Cite
|
Sign up to set email alerts
|

Mitral valve replacement in a patients with an extensively calcified mitral anulus: Report of a case

Abstract: We report herein the case of a patient with chronic renal failure in whom mitral valve stenosis with extensive mitral anular calcification involving the entire anulus and leaflets was successfully treated surgically. Excision of both leaflets and partial resection of the anular calcification enabled the insertion of a 23-mm St. Jude Medical prosthetic valve. The technical difficulties involved with inserting the appropriate-sized prosthetic valve in a narrowed mitral anulus with heavy calcification are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…When MAC limits the annulus and an appropriate‐sized prosthesis can be inserted, the prosthetic valve can be secured onto the mitral leaflet itself 2 . When a partial debridement of MAC makes it possible to implant an appropriate‐sized prosthetic valve, the usual MVR suturing the valve onto the calcified annulus sometimes causes perivalvular leakage and valve dehiscence 3,4 . Carpentier et al described the “sliding atrioplasty,” which includes the complete removal of MAC and suturing the LA wall to the LV wall covering the annular area, and they performed an MVR after this procedure for cases with extensively developed MAC 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…When MAC limits the annulus and an appropriate‐sized prosthesis can be inserted, the prosthetic valve can be secured onto the mitral leaflet itself 2 . When a partial debridement of MAC makes it possible to implant an appropriate‐sized prosthetic valve, the usual MVR suturing the valve onto the calcified annulus sometimes causes perivalvular leakage and valve dehiscence 3,4 . Carpentier et al described the “sliding atrioplasty,” which includes the complete removal of MAC and suturing the LA wall to the LV wall covering the annular area, and they performed an MVR after this procedure for cases with extensively developed MAC 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In a case with severe MAC, it is very important to secure the prosthetic valve so as not to cause any perivalvular leakage. For this reason, suturing the prosthesis onto the annulus where the calcification remains should be avoided, because such procedure eventually results in perivalvular leakage and prosthetic valve dehiscence 3,4 . David et al devised the mitral annular reconstruction using a pericardial patch, and reported an excellent long‐term result of this procedure 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a different methodology, VIRMANI et al [13] affirmed that, in this subgroup of patients, the distance between the structures in question, in the proximal portion of the circumflex artery, is 8.4 mm.…”
Section: Commentsmentioning
confidence: 99%
“…However, there have been few works that analysed this anatomical relationship, just as the numbers of patients that have been studied is small [1,2,[5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%